Pillsbury's 'A' Mill, the Largest Flour Mill in the World, Minneapolis, Minnesota' - postcard - NC (Wikimedia Commons, 2026)
Carte postale ancienne issue de Wikimedia Commons. Titre : '"Pillsbury's "A" Mill, the Largest Flour Mill in the World, Minneapolis, Minnesota" - postcard'. Cette image a été intégrée comme vue documentaire dans le fonds.
Droits : Image diffusée via Wikimedia Commons
Keywords: Industrie et techniques; carte postale; image ancienne; Économie